(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. Parts of speech have been studied for more than one millennium and are among those fundamental concepts of linguistics that have proven their right to exist by their long-term use in descriptions of different languages ​​and grammars of various types, from school to academic. They are certainly among the most fully described categories of words, for in every grammar and every dictionary of a single language, some decision must be made regarding the number and nomenclature of the parts of speech represented in it. Meanwhile, the question of parts of speech as special categories or classes of words, the boundaries of these classes and the very principles of their selection, is one of the questions that have a long history of study, however, still does not belong to the number of resolved ones. Аннотация.Части речи изучаются уже не одно тысячелетие и входят в число тех фундаментальных понятий лингвистики, которые доказали свое право на существование длительным их использованием в описаниях разных языков и грамматиках разного типа, начиная от школьных и кончая академическими. Они, безусловно, принадлежат к числу наиболее полно описанных разрядов слов, ибо в каждой грамматике и каждом словаре отдельно взятого языка должно быть принято какое-либо решение относительно числа и номенклатуры представленных в нем частей речи. Между тем вопрос о частях речи как особых категориях или классах слов, о границах этих классов и самих принципах их выделения, хотя и относится к числу вопросов, имеющих давнюю традицию их изучения, все же не принадлежит к числу решенных.